Implementation of the Business Judgement Rule Doctrine as Legal Protection for Directors in Realizing Good Governance of Regionally-Owned Enterprises - Hamzar Nodi; Ramlan Ramlan; Ida Hanifah (Faculty of Law, Universitas Pekalongan, 2023)
The form of BUMD governance as a regional company as regulated in UUPD and PPBUMD consists of Regional Public Companies (Perumda) and Regional Limited Companies (Perseroda). The establishment of Perumda is in the form of regional regulations based on regional needs and the feasibility of the business field of the Perumda to be formed. Perumda is a BUMD whose entire capital is owned by one region only and is not in the form of shares. One of the important organs in a company is the board of directors. The board of directors who control the company in daily activities has the authority to determine policies in carrying out its powers and obligations in managing the company must have good intentions, be responsible, have integrity, be honest, and be highly dedicated to advancing and developing the company. The board of directors is fully responsible personally for the company's losses if the person concerned is guilty or negligent in carrying out his duties. The board of directors can take or carry out actions to facilitate his duties as long as it is within the scope of his duties and obligations and does not conflict with customs, fairness, and propriety. Implementation of the business judgment rule (BJR) doctrine as a form of protection given to directors in carrying out their duties and responsibilities in running the company. Business decisions or actions taken by directors are intended to manage the company professionally according to their expertise to generate profits for the company, even though there are risks from these decisions and actions that can cause losses for the company